2008
DOI: 10.1001/archneurol.65.8.noc80042
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Disease Activity and Disability With High-Dose Cyclophosphamide in Patients With Aggressive Multiple Sclerosis

Abstract: To explore the safety and effectiveness of high-dose cyclophosphamide (HiCy) without bone marrow transplantation in patients with aggressive multiple sclerosis (MS). Design: A 2-year open-label trial of patients with aggressive relapsing-remitting multiple sclerosis (RRMS) given an immunoablative regimen of HiCy (50 mg/kg/d for 4 consecutive days) with no subsequent immunomodulatory therapy unless disease activity reappeared that required rescue therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…High-dose cyclophosphamide is a highly immunosuppressive agent that, in addition to its successful use as a treatment for aplastic anemia [9][10][11] and other severe refractory autoimmune diseases, 14,16,21,22 has proven efficacy in allogeneic BMT as both a conditioning regimen 23 and graft-versus-host disease prophylaxis. 24 Cyclophosphamide's unique metabolism is responsible for its immunosuppressive yet stem cell-sparing properties.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose cyclophosphamide is a highly immunosuppressive agent that, in addition to its successful use as a treatment for aplastic anemia [9][10][11] and other severe refractory autoimmune diseases, 14,16,21,22 has proven efficacy in allogeneic BMT as both a conditioning regimen 23 and graft-versus-host disease prophylaxis. 24 Cyclophosphamide's unique metabolism is responsible for its immunosuppressive yet stem cell-sparing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although approaches differ we have most typically given an in-hospital induction regimen with 3-5 days of recurrent therapy. A report by Krishnan et al [33] describes an induction regimen of 50 mg/kg/day of cyclophosphamide for 4 days with granulocyte colony-stimulating factor to rescue neutrophils. Enrolled patients were required to have consecutive active MRIs, at least 1 clinical exacerbation in the year prior to high-dose cyclophosphamide treatment, or a sustained increase of 1 point or higher on the Expanded Disability Status Scale (EDSS) in the preceding year.…”
Section: Inductionmentioning
confidence: 99%
“…96 A more recent trial demonstrated the benefit of high-dose cyclophosphamide (50 mg/kg per d for 4 consecutive days, followed by granulocyte colony-stimulating factor 6 days after completion) in 9 patients with aggressive RRMS, 8 of whom had not responded to conventional steroid therapy. 97 Although this study was conducted in patients who had clinical exacerbations between 6 and 12 months prior to enrollment, and actually excluded patients who had a flare in the 3 months prior to cyclophosphamide administration, one might extrapolate that cyclophosphamide could be utilized as a rescue treatment for acute fulminant relapses. Safety concerns with the use of short-term high-dose cyclophosphamide monotherapy in patients with MS include neutropenia and infection.…”
Section: Acute Treatment Of Cis-what Every Neurohospitalist Needs To mentioning
confidence: 99%